Physicochemical and bilogical characterization of soils from the vicinity of the Arctowski Polish Antarctic Station - Białkowska, Aneta; Grzelczyk, Anna; Długołęcka, Anna; Cieśliński, Hubert; Kalinowska, Halina; Kur, Józef; Turkiewicz, Marianna (Wydawnictwo Politechniki Łódzkiej, 2012)
Soil samples collected in 2006 from 4 different sites (Puchalski Hill and a moraine below this hill, an elephant seal colony and a penguin rookery) in the vicinity of Arctowski Polish Antarctic Station at King George Island were characterized in terms of physicochemical properties (pH, humidity, concentration of selected inorganic and organic substances), microbial colonization and the overall activity of selected enzymes (differentglycosidases and esterases). Activity of the latter enzymes was assayed by p-nitrophenyl and 4-methylumbelliferone derivatives of fatty acids (by spectrophotometric and fluorimetric method, respectively). The highest lipolytic activity was found in soils from the elephant seal colony and penguin rookery.